A Comprehensive Framework for ML Model Validation: From Development to Production Monitoring in Search and Recommendation Systems - Siddharth Pratap Singh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive framework for validating, testing, and debugging machine learning models throughout their lifecycle, emphasizing search and recommendation systems. The article introduces a three-phase validation approach encompassing offline validation, pre-production testing, and production monitoring, addressing the unique challenges posed by dynamic data distributions and evolving user behaviors. The framework incorporates robust test set construction, counterfactual evaluation techniques, and automated debugging tools while emphasizing the importance of continuous monitoring and interpretability in production environments. The article demonstrates the framework’s effectiveness in maintaining model performance and reliability through case studies across financial trading, content moderation, dynamic pricing, and real-time bidding systems. The article also presents novel approaches to automated root cause analysis and drift detection, contributing to developing more resilient machine learning systems. The proposed framework advances the field by bridging the gap between theoretical validation methods and practical implementation challenges in production environments, providing practitioners with actionable guidelines for ensuring model quality across the entire development pipeline.